Optical Coherence Tomography Angiography Macular and Peripapillary Vessel Perfusion Density in Healthy Subjects, Glaucoma Suspects, and Glaucoma Patients - Triolo, Giacinto; Rabiolo, Alessandro; Shemonski, Nathan D.; Fard, Ali; Di Matteo, Federico; Sacconi, Riccardo; Bettin, Paolo; Magazzeni, Stephanie; Querques, Giuseppe; Vazquez, Luis E.; Barboni, Piero; Bandello, Francesco (Investigative ophthalmology & visual science, 2017)
To evaluate macular and peripapillary vessel perfusion density (VD) in glaucoma suspects (GS) and glaucoma patients; to correlate ganglion cell-inner plexiform layer (GCIPL) and retinal nerve fiber layer (RNFL) thicknesses with macular and peripapillary VD; and to evaluate the diagnostic accuracy of the structural and vascular parameters. A consecutive series of GS, glaucoma patients, and healthy subjects was prospectively recruited from July 1, 2016, to January 31, 2017. All subjects underwent standard automated perimetry, spectral-domain optical coherence tomography (OCT), and 6 × 6-mm optical coherence tomography angiography (OCT-A) centered on the fovea and optic nerve. Forty controls, 40 GS, and 40 glaucoma patients were enrolled. Peripapillary RNFL, GCIPL, and macular RNFL thicknesses significantly decreased in the glaucoma group compared to controls and GS (P < 0.01). Peripapillary VD in average and in the superior and inferior quadrants decreased in the glaucoma group (P ≤ 0.001); conversely, macular VD was not statistically different across groups (P > 0.05). At the peripapillary area, a correlation between RNFL thickness and VD was found; conversely, no statistically significant correlation was found between GCIPL thicknesses and macular VD (all P > 0.05) in all groups. Peripapillary RNFL and GCIPL showed higher diagnostic capacity compared to peripapillary and macular VDs. Structural damage is evident both in the peripapillary and in macular areas. Vascular damage seems to be less prominent, as it was seen only for the glaucoma group and at the radial peripapillary plexus. Diagnostic abilities are excellent for structural variables, less so but still good for peripapillary VD, and poor for macular VD.